2017
DOI: 10.1002/adem.201700094
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Spot Welding of Nickel Foam Sheet and Aluminum Solid Sheet

Abstract: Nickel foam sheet composed of three-dimensional (3D) triangular struts and aluminum solid sheet are welded via ultrasonic spot welding. The foam underwent acceptable thickness reduction and deformation, whereas most of the porous structures remain intact. Energy dispersive spectroscopy (EDS) analysis shows that little interdiffusion is noticed across the welding interface, leading to the formation of only a small amount of solid solution, and intermetallic compounds. Infrared temperature measurements show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…One of these effects, called "acoustoplastic," is a temporary softening due to the imposing ultrasound during the plastic deformation of metallic materials. [1] Considering this effect, ultrasound is suitable for use in several manufacturing processes such as welding, [2,3] additive manufacturing, [4,5] surface impact treatment, [6,7] and metal forming. [8,9] The stress reduction caused by acoustoplastic can be divided into stress superposition, dynamic impact, and acoustic softening.…”
Section: Introductionmentioning
confidence: 99%
“…One of these effects, called "acoustoplastic," is a temporary softening due to the imposing ultrasound during the plastic deformation of metallic materials. [1] Considering this effect, ultrasound is suitable for use in several manufacturing processes such as welding, [2,3] additive manufacturing, [4,5] surface impact treatment, [6,7] and metal forming. [8,9] The stress reduction caused by acoustoplastic can be divided into stress superposition, dynamic impact, and acoustic softening.…”
Section: Introductionmentioning
confidence: 99%
“…Scanning electron microscopy (SEM) was used to observe the morphology of ultrasonic weld joint and fracture, and component analysis was carried out in combination with the cross-section of EDS interface of joint. Xie et al 76 used ultrasonic welding to join aluminium solid sheet with nickel foam and observed the weld joints. As shown in Figure 13, the SEM photograph can clearly show the joint interface of aluminium and nickel foam, and the mechanical lock occurs at some area of the welding interface.…”
Section: Non-in Situ Testingmentioning
confidence: 99%
“…SEM images of the Al/Ni foam weld interface at different welding energies and EDS line scan results (yellow arrows show the scanning direction): (a) 10 J, (b) 30 J, (c) 50 J and (d) 70 J. 76 …”
Section: Non-in Situ Testingmentioning
confidence: 99%
See 1 more Smart Citation